Dichotomous Effect of Caffeine, Curcumin, and Naringenin on Genomic DNA of Normal and Diabetic Subjects - Debarati Chattopadhyay; Ashok Somaiah; Divya Raghunathan; Kavitha Thirumurugan (Scientifica)
Nutraceutical compounds show antioxidant and prooxidant properties under stress conditions like cancer, diabetes, and other diseases. The objective of this study is to find the dichotomic behavior of caffeine, curcumin, and naringenin on DNA of diabetic and normal subjects in the presence and absence of copper, hydrogen peroxide, and complex of copper-hydrogen peroxide. Hydrogen peroxide releases hydroxyl free radicals (•OH) on oxidation of Cu (I) to Cu (II) through Fenton-type reaction to cause DNA damage. In the results, agarose gel electrophoretic pattern speculates the prooxidant effect of caffeine and antioxidant effect of curcumin on DNA in the presence of copper and hydrogen peroxide. UV-Vis spectral analysis shows hyperchromism on addition of DNA to caffeine, hypochromism with curcumin, and subtle changes with naringenin. The chosen nutraceuticals act as inducers and quenchers of oxidative free radicals arising from diabetes.